2017
DOI: 10.1073/pnas.1714522114
|View full text |Cite
|
Sign up to set email alerts
|

Multiple oscillatory rhythms determine the temporal organization of perception

Abstract: SignificanceTo reduce the complexity of our sensory environment, the perceptual system discretizes information in different ways. In the time domain, this is evident when stimuli that are presented very close in time are sometimes faithfully perceived as different entities, whereas they are integrated into a single event at other times. Using multivariate decoding of electroencephalography data, we show that integration and segregation of stimuli over different time scales (a few tens vs. a few hundreds of mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 65 publications
10
96
1
2
Order By: Relevance
“…In particular, phase yielded strongly significant (p<0.001) decoding results in 9/10 subjects for the hard discrimination, while power did so only in 4/10 subjects. Primacy of phase information over power information, especially for distinguishing between activity patterns corresponding to different sensory stimuli, is in accordance with several prior reports in auditory, visual and tactile modalities (Luo and Poeppel, 2007;Howard and Poeppel, 2010;Ng et al, 2013;Gross et al, 2013;Schyns et al, 2011;Ronconi et al, 2017;Wang et al, 2018;Baumgarten et al, 2015), in motor signals (Hammer et al, 2013), as well as in more complex paradigms involving working memory and decision making (Rizzuto et al, 2003;Lopour et al, 2013). In our dataset and for the binary decoding analyses we considered, the combination of power and phase did not convey additional information beyond the one conveyed by the most informative between power and phase ( Fig.…”
Section: Stimulus Encoding Occurs Preferentially At Delta-theta and Gsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, phase yielded strongly significant (p<0.001) decoding results in 9/10 subjects for the hard discrimination, while power did so only in 4/10 subjects. Primacy of phase information over power information, especially for distinguishing between activity patterns corresponding to different sensory stimuli, is in accordance with several prior reports in auditory, visual and tactile modalities (Luo and Poeppel, 2007;Howard and Poeppel, 2010;Ng et al, 2013;Gross et al, 2013;Schyns et al, 2011;Ronconi et al, 2017;Wang et al, 2018;Baumgarten et al, 2015), in motor signals (Hammer et al, 2013), as well as in more complex paradigms involving working memory and decision making (Rizzuto et al, 2003;Lopour et al, 2013). In our dataset and for the binary decoding analyses we considered, the combination of power and phase did not convey additional information beyond the one conveyed by the most informative between power and phase ( Fig.…”
Section: Stimulus Encoding Occurs Preferentially At Delta-theta and Gsupporting
confidence: 91%
“…The relationships between spectral features of neural activity and its stimulus encoding properties is a topic of great interest in sensory neuroscience (e.g., (Belitski et al, 2008;Belitski et al, 2010;Tsuchiya et al, 2008;Schyns et al, 2011;Gross et al, 2013;Ronconi et al, 2017)). The development of a neuronal network model that exhibits remarkable correspondence to iEEG data in terms of both spectral properties and stimulus encoding enabled us to formulate an approach for relating these two aspects of neural activity, which have hitherto been mostly investigated separately.…”
Section: Model-derived Relationships Between Spectral Features and Stmentioning
confidence: 99%
“…1A). For instance, in both visual and somatosensory systems, the detection of a near-threshold stimulus and the ability to distinguish two rapidly presented stimuli correlate with EEG/MEG phase (Ai and Ro, 2014;Baumgarten et al, 2015;Busch et al, 2009;Milton and Pleydell-Pearce, 2016;Ronconi et al, 2017). In these studies, stimuli are often presented at an a-priori unknown, random neural phase in each trial; this leads to the possibility of testing how performance depends on the phase of spontaneous (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…the null distribution). This distribution can, for instance, be constructed by repeatedly shuffling performance labels (e.g., "hits" vs "misses") and re-running the original analysis on the permuted datasets (Busch et al, 2009;Dugué et al, 2011;Hanslmayr et al, 2013;Ng et al, 2012;Ronconi et al, 2017;Strauß et al, 2015;ten Oever and Sack, 2015;Wutz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that perception is discrete and cyclic in a manner of perceptual cycles [15,16,41,54,55]. Accumulating recent evidence showed that perceptual performance depends on the frequency of the critical rhythm at around the onset time of stimuli [46,47,56]. A higher frequency of the brain oscillations should be equivalent to a faster frame rate of discrete perception, and vice versa.…”
Section: Discussionmentioning
confidence: 99%